How to Attain Enlightenment? The Pramāṇa and the Chan Schools on the Practice of Meditation - Woo, Jeson (Religions, 2024)
Throughout the history of Buddhism, the main goal of Buddhists has been to attain enlightenment. This paper investigates how the Pramāṇa and the Chan schools define enlightenment and their ways of attaining it. The Pramāṇa school deals with enlightenment and problems relevant to it in terms of yogipratyakṣa, or the intuition of an omniscient being (sarvajña). On the other hand, the Chan school developed gongan meditation, which leads to enlightenment by contemplating a huatou, the key phrase of a gongan. This paper focuses on examining and comparing the following issues in these two schools: (1) the motivations for seeking enlightenment, (2) the role of meditation in each, and (3) the process of attaining enlightenment.